The role of online media in mobilizing large-scale collective action - Chen, Zhuo (2021)
This study investigates the role of online media in mobilizing large-scale collective action. Adopting the theoretical framework of collective action space, we formulated the organizing process of collective action into a model with two dimensions—hierarchy and closure—and analyzed how they influence mobilization. The model was tested against Twitter data collected during the 2020 Hong Kong protest, including a total of 54,365 tweets posted by 14,706 distinct users between 1 May and 31 May 2020. Social networks analysis metrics—k-coreness and brokerage of individual users in their following networks—were employed to quantify the organizing process of the protest and estimate their effects on message virality. The results showed that messages generated by users who occupied peripheral positions (i.e., lower k-coreness) and by those connecting others within closed communities (i.e., lower brokerage) were more likely to diffuse than those generated by central users or those who bridged different communities. That is, online media facilitate mobilization in a decentralized yet fragmented fashion. This article concludes with a discussion of the theoretical implications of the current findings and suggests the directions for future research on collective action on online media.